Assessment of the impact of pregnancy and malaria infection on the variation of neutrophil levels in women from San, Mali - Moussa Djimde; Charles Arama; Bouréma Koné; Hamadoun Diakité; Mohamed Keita; Mamadou D Samaké; Bréhima Tembely; Balla Bagayoko; Mohamed B Traoré; Japhet K Tshiongo; Hypolite M Mavoko; Alassane Dicko; et al. (Journal of Infection in Developing Countries)
Background: In patients with severe neutropenia, infections can rapidly become serious and life-threatening. It is essential to understand whether pregnancy induces changes in neutrophil levels thereby posing an increased threat to the health of gravidae.